Life-History Traits and Genetic Characterization of Polystoma borellii (Monogenea, Polystomatidae), a Parasite of Pleurodema borellii (Anura, Leptodactylidae) - Carolina Davies; Juan José Lauthier; Matías Martín Renfijes; Ivanna Gabriela Cruz; Dora Davies (Parasitologia, 2025)
The genus Polystoma includes parasites with direct life cycles that involve a short-lived free-living, aquatic oncomiracidia, post-larvae infecting the gill chambers of tadpoles, and adults parasitizing the urinary bladder of adult anurans. Despite the high diversity of anurans in the South American sub-continent, less than 20 species of Polystoma have been reported to date, and, particularly, in Argentina, only five species have been described from adult frogs. The aim of this work was to describe and characterize taxonomically the specimens found parasitizing tadpoles and frogs living in a well in Chicoana, Salta province, Argentina. Parasites were observed under optical and scanning electron microscopy and characterized genotypically by sequencing ITS1 and COI fragments. Frogs and tadpoles were characterized by morphology and sequencing a partial fragment of the cytochrome B region, confirming that the hosts corresponded to Pleurodema borellii. Given their morphology and the strict specificity of Polystoma species for their hosts, the identity of the parasites was established as P. borellii. The morphology of oncomiracidia and post-larvae was described, expanding adults’ description with insights provided by COI and ITS1 molecular analysis. The present work summarizes a complete description of the life cycle, with the genetic characterization of Polystoma borellii in Salta, Argentina.